ЕКСПЕРИМЕНТАЛЬНЕ ДОСЛІДЖЕННЯ РОЗВИТКУ ОСОБИСТОСТІ ДИТИНИ В КОЛЕКТИВІ (НА ПРИКЛАДІ ДИТЯЧОГО БУДИНКУ-ЛАБОРАТОРІЇ «МІЖНАРОДНА СОЛІДАРНІСТЬ») - Шпичак, Інна (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті здійснено реконструювання особливостей виховання дітей дошкільного віку у колективі на прикладі Дитячого будинку-лабораторії «Міжнародна солідарність», який діяв у Москві 1921–1925 рр. Розкрито принципи побудови виховного процесу у даному закладі. Підкреслено зв’язок розвитку психоаналізу із загальнодержавною політикою у Радянській державі. Охарактеризовано важливі аспекти розвитку дитячої психіки у ранньому віці. Проаналізовано психоаналітичні підходи до виховання у спадщині психоаналітика і педагога В. Ф. Шмідт. В статье осуществлена реконструкция особенностей воспитания детей дошкольного возраста в коллективе на примере Детского дома-лаборатории «Международная солидарность», который действовал в Москве 1921–1925 гг. Раскрыты принципы построения воспитательного процесса в данном учреждении. Подчеркнуто связь развития психоанализа с общегосударственной политикой в Советском государстве. Охарактеризованы важные аспекты развития детской психики в раннем возрасте. Проанализированы психоаналитические подходы к воспитанию в наследстве психоаналитика и педагога В. Ф Шмидт. An actual point of the topic, discovered in the article is due to the tendency towards the increase of demand for the education and training of high quality, renewal of forms and methods of the educational process organization at educational institutions and significance of resort to the scientific investigations of historiographical type. There were some modifications realized in this article in the field of education of the underschool age children in team as for example children’s home-laboratory «International Solidarity» which worked in 1921–1925 in Moscow. Some characteristics of the structure of educational process were discovered in the institution. Interrelation of psychoanalysis development and state policy was underlined in the Soviet state. The important aspects of children psyche formation at the early age were described. Psychoanalytical approach to the training was analyzed also in works of the psychoanalyst and pedagogue V. F. Shmidt. There are put some major pedagogical demands concerning to the training of little children for the sake of their successive healthy development and life in community.